1976
DOI: 10.1115/1.3450560
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Velocity and Temperature Fields in a Flow-Through Reservoir

Abstract: The fluid dynamic and temperature fields in a reservoir are numerically simulated by means of a finite difference procedure. The flow in the rectangular reservoir is assumed to be two-dimensional in a vertical plane. Inflow is allowed at the surface on one end of the reservoir and outflow occurs at any depth on the opposite end. The reservoir inflow is set at a given temperature and velocity so as to simulate the thermal discharge from a power generating facility. At the surface of the reservoir wind shear, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…These figures show some very interesting features, particularly with respect to the isotherms as Gr/Re2 changes. Similar trends were observed for other values of the governing parameters and the observed behaviour agrees qualitatively with the results of Oberkampf and Crow (1976) and Cabelli (1977).…”
Section: Numerical Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These figures show some very interesting features, particularly with respect to the isotherms as Gr/Re2 changes. Similar trends were observed for other values of the governing parameters and the observed behaviour agrees qualitatively with the results of Oberkampf and Crow (1976) and Cabelli (1977).…”
Section: Numerical Resultssupporting
confidence: 90%
“…The flow considered here is the one that arises due to horizontal inflow and outflow in a wide tank, so that the problem may be considered as two-dimensional. Oberkampf and Crow (1976) and Cabelli (1977) have considered some flows related to this problem. The transient problem is of particular interest in energy storage systems and the spread of the thermal field, outwards from the inflow, is to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In these instances, the interaction between forced and free convection becomes important as shown, for instance, by Chan et al [9]. Mixed convection occurring in water bodies like lakes and ponds due to thermal discharges is studied by Oberkampf and Crow [10], who have systematically taken into account the effects of inflow/outflow, wind shear, buoyancy and heat losses from the surface by convection, evaporation and radiation. In air-conditioned rooms, the buoyancy created due to human occupancy influences the forced air circulation to a significant extent as reported by Nielsen et al [11].…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, the studies on natural convective ow in a partially open enclosure have received considerable attention. Many authors have reported their studies on this problem including Oberkampf and Crow [16], Sparrow and Samie [17], Cha and Jaluria [18], Oosthuizen and Paul [19], Papanicolaou and Jaluria [20]. They pointed out that convective heat transfer in a partially open cavity causes a dramatic di erence in the recirculation cavity ow and thermal ÿeld.…”
Section: Introductionmentioning
confidence: 98%